A Comparative Mass Spectrometric Study of Fatty Acids and Metals in Some Seed Extracts. Issue 5 (October 2016) - Şuvar, S.; Bleiziffer, R.; Podea, P.; Iordache, A.; Voica, C.; Zgavarogea, R.; Culea, M.
A major cause of cardiovascular diseases and cancer is diet content, so optimization of micronutrients in food is very important. Omega-3 fatty acids supplementation for patients has beneficial effects on subjective global assessment score and metabolic profiles. Fatty acid content and the metal ions in different seeds (linseed, poppy, grape, hemp, nuts, pumpkin, sesame, watermelon, chia) recommended as food supplements and purchased on the Romanian market, were compared. Gas chromatography coupled to mass spectrometry was used for fatty acid identification and quantitation, and inductively coupled plasma mass spectrometry for analytical measurements of metals.